(untitled) (Tabularium Historiae, 2019)
Modestus, the praetorian prefect of the Orient uncovered details of magical practices in high places, using information supplied by Palladius, a humble poisoner, and Heliodorus, an expert in horoscopy. It was claimed that a certain Fidustius, assisted by two accomplices , had actually sought and ascertained the name of the emperor’s succesor through supernatural agencies. This man was to be one Theodorus, an educated and charismatic notarius from Gaul.